The Role of Presented Objects in Deriving Color Preference Criteria from Psychophysical Studies. Issue 3 (3rd July 2017) - Royer, Michael P.; Wei, Minchen
ABSTRACT:  Although it is a critical component of any measure of color rendition, a standardized set of color samples can seldom perfectly match a real space or a real set of observed objects. This means that there will always be some level of mismatch between predicted and observed color shifts. This article explores how the color distortions of three object sets that could be used in experiments compare to the color distortions predicted using the color evaluation samples of IES TM-30-15 (TM-30). The experimental object sets include those from a recent experiment [Royer and colleagues 2016], a set of produce (10 fruits and vegetables), and the X-Rite ColorChecker Classic. This numerical analysis focuses on the range of differences between viewed and characterized color shifts—using the TM-30 fidelity index ( R f ), the TM-30 gamut index ( R g ), and an alternative to R g based on ΔC in CIECAM02—over a set of 344 spectral power distributions. The differences depended on the average chroma and spectral features of the sample set. The substantial range of differences shown for the produce and the ColorChecker means that design criteria for color rendition derived using these sample sets are less reliable. Specifiers should carefully consider how average measures of color rendition are applied to real spaces, and experimenters should carefully select experimental objects to avoid mischaracterizations.